ADSORPSI LOGAM KADMIUM (Cd) MENGGUNAKAN ADSORBEN AMPAS TEH DENGAN METODE CELUP - Tiara Izza Nafila; Bohari Yusuf; Teguh Wirawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
Tea waste adsorbent can be utilized for cadmium metal adsorption. The aim of this study was to determine the optimumcontact time, optimum pH, and maximum adsorption capacity using the batch method and the dip method. The concentration of cadmium was determined by complexing using dithizone and measured using a UV-Vis spectrophotometer at a wavelength oh 518 nm. The results were obtained in the batch method at the optimum contact tme of 10 minutes, the optimum pH of 10, and teh maximum adsorption capacity of 157,1282 mg/g. in the dip method the optimum contact time was 30 minutes, and the maximum adsorption capcity was 76,7932 mg/g. the type of isotherm obtained on the adsorption of cadmium metal oh the tea dregs adsorbent was the Langmuir isotherm. Keywords: Tea dregs, adsorption, cadmium, dip method